2013
DOI: 10.1063/1.4799833
|View full text |Cite
|
Sign up to set email alerts
|

Efficient inverted polymer solar cells with thermal-evaporated and solution-processed small molecular electron extraction layer

Abstract: Efficient inverted polymer solar cell is reported upon by integrating with a small molecular 1,3,5-tri(phenyl-2-benzimi-dazolyl)-benzene (TPBi) electron extraction layer (EEL) at low processing temperature with thermal-evaporation and solution-process, resulting in the power conversion efficiencies of 3.70% and 3.47%, respectively. The potential of TPBi as an efficient EEL is associated with its suitable electronic energy level for electron extraction and hole blocking from the active layer to the indium tin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Energy level diagram for ITO, PEDOT:PSS, PVK, histidine‐doped MoS2 QDs, TPBi, and Ag before contact, and illustrated band diagram for /ITO/PEDOT:PSS/PVK/histidine‐doped MoS2 QDs/TPBi/Ag heterostructure under equilibrium are shown in Figure a,b. The positions of the highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO) levels, workfunctions of PEDOT:PSS, PVK, TPBi, work function of Ag electrode and electron affinity of the MoS 2 were adopted from the previous works . The work function of histidine‐doped MoS 2 QDs was measured by SKPM as shown in Figure S1a,b (Supporting Information).…”
mentioning
confidence: 99%
“…Energy level diagram for ITO, PEDOT:PSS, PVK, histidine‐doped MoS2 QDs, TPBi, and Ag before contact, and illustrated band diagram for /ITO/PEDOT:PSS/PVK/histidine‐doped MoS2 QDs/TPBi/Ag heterostructure under equilibrium are shown in Figure a,b. The positions of the highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO) levels, workfunctions of PEDOT:PSS, PVK, TPBi, work function of Ag electrode and electron affinity of the MoS 2 were adopted from the previous works . The work function of histidine‐doped MoS 2 QDs was measured by SKPM as shown in Figure S1a,b (Supporting Information).…”
mentioning
confidence: 99%
“… 9 For instance, even if the W F of the metal anode is small, such as that of Al with W F = 4.3 eV, when this metal is coupled with MoO 3 , the hybrid electrode Al/MoO 3 is very efficient in extracting holes. 10 Therefore, in the present work, we used MoO 3 as the HTL and we focused our interest on the cathode/electron acceptor interface. We show that it is possible to improve very significantly the inverted OPV performance using an original hybrid buffer layer.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the anode, it is necessary to have a high W F , and MoO 3 , with W F ≥ 5.3 eV, is a very efficient hole-transporting layer (HTL) . For instance, even if the W F of the metal anode is small, such as that of Al with W F = 4.3 eV, when this metal is coupled with MoO 3 , the hybrid electrode Al/MoO 3 is very efficient in extracting holes . Therefore, in the present work, we used MoO 3 as the HTL and we focused our interest on the cathode/electron acceptor interface.…”
Section: Introductionmentioning
confidence: 99%
“…Since ITO covered the whole glass substrates, some ITO must be removed to obtain the under electrode. After masking a broad band of 25 mm by 20 mm, the ITO was etched by using Zn powder + HCl as etchant [8,9]. After scrubbing with soap, the ITO coated substrates were rinsed in running deionised water.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of inverted OPVCs (IOPVCs) it was shown that the use of a MoO 3 layer thick of 6 nm allows obtaining efficient hole collection whatever is the metal of the anode [8,9]. The main aim of the present work being the study of the interface cathode/EA, we have used this classical MoO 3 /anode hole collecting structure, with Al metal electrode.…”
Section: Introductionmentioning
confidence: 99%